Fundamental Solution of Elliptic Equation with Positive Definite Matrix Coefficient - Khoirunisa, Khoirunisa; Karim, Corina (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2018)
In this paper, we study the fundamental solution of elliptic equations with real constant coefficients Â where is a positive definite matrix. We obtained by searching the radial solution so that we solved the equation into ordinary differential equations.Â